Molecular dynamics simulations of mixed DOPC-ß-sitosterol bilayers and their interactions with DMSO - Hughes, Zak; Mancera, Ricardo (RSC Publishing, 2013)
ell membrane phospholipid bilayers can be damaged by the large amounts of dimethyl sulphoxide (DMSO) commonly used in cryopreservation. The interaction of DMSO with model bilayers consisting of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) and ß-sitosterol has been studied using molecular dynamics simulations. Initially the effect of sterol concentration and temperature upon bilayers solvated in pure water was determined, and membranes containing ß-sitosterol were compared with membranes containing cholesterol. These simulations showed that the presence of sterols has a condensing effect on the phospholipids, causing a reduction in the area per lipid as the sterol concentration increases, up to a phospholipid–sterol ratio of 2[thin space (1/6-em)]:[thin space (1/6-em)]1. The incorporation of sterols into the bilayer also increased the thickness and order of the phospholipid acyl tails. DOPC–ß-sitosterol bilayers at different relative concentrations were simulated in solutions of 2.5 and 25.0 mol% DMSO. The interaction of DMSO with the bilayers caused the bilayers to expand laterally, while thinning normal to the plane of the bilayer expansion. The same qualitative behaviour has been shown to occur in pure phosphocholine bilayers. However, the presence of sterols made the membranes more resistant to the effects of DMSO, to the extent that the membranes where able to maintain their integrity in 25.0 mol% DMSO, a concentration that would otherwise cause the destruction of a pure DOPC bilayer. Increasing the concentration of ß-sitosterol within the bilayers reduced the rate of DMSO diffusion across the bilayer and, if the concentration was large enough, caused the diffusion mechanism to change. DMSO was observed to disorder the membranes enough to cause an increase in the number of sterol “flip–flops”. The findings of this work provide a more realistic description of how DMSO interacts with cell membranes and the role of the composition of the membrane.